Evaluasi Kepuasan Mahasiswa Terhadap Kualitas Pendidikan Lembaga Pendidikan Tinggi ABC di Cikarang - Farliana Sutariah (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2017)
Education is one service industry that provides services to students in need. One of Institute from Cikarang, Bekasi, west Javaorganized and developed the science, technology, and as a scientific community that is full ofsublime imagery and educate the nation's life. The real conditions encountered by Institute is currently at in providing services to students especially on teaching staff (lecturers) as well asacademic staff not yet optimal. An increase in the quality of service can be implemented using approach servqual. Servqual is a method for measuring the quality of service from a service provider. Quality of service is measured from each dimension (tangible, responsiveness, reliability, assurance, Empathize). For the result we know 5 element spread on 4 quadrant. Quadrant 1 are spread 6 things, Quadrant II are spread 11 thing, Quadrant III are spread 9 things and last Quadrant IV are spread 4 things. We investigate cause that need  problem solving on Institute by Root Cause Analyze (RCA.)Based on the results of calculation and pay attention to the real conditions, interviews with students,obtained significant complaints with the research. In this case the Institute should improvethe quality of service, both in terms of performance of teaching staff, and the number of teaching staff for teachingand learning process can be going well, so does the relationship of administration and facility staff and othersupporting improved.